Towards nationally curated data archives for clinical radiology image analysis at scale: Learnings from national data collection in response to a pandemic. (November 2021) - Cushnan, Dominic; Berka, Rosalind; Bertolli, Ottavia; Williams, Peter; Schofield, Daniel; Joshi, Indra; Favaro, Alberto; Halling-Brown, Mark; Imreh, Gergely; Jefferson, Emily; Sebire, Neil J; Reilly, Gerry; et al.
The prevalence of the coronavirus SARS-CoV-2 disease has resulted in the unprecedented collection of health data to support research. Historically, coordinating the collation of such datasets on a national scale has been challenging to execute for several reasons, including issues with data privacy, the lack of data reporting standards, interoperable technologies, and distribution methods. The coronavirus SARS-CoV-2 disease pandemic has highlighted the importance of collaboration between government bodies, healthcare institutions, academic researchers and commercial companies in overcoming these issues during times of urgency. The National COVID-19 Chest Imaging Database, led by NHSX, British Society of Thoracic Imaging, Royal Surrey NHS Foundation Trust and Faculty, is an example of such a national initiative. Here, we summarise the experiences and challenges of setting up the National COVID-19 Chest Imaging Database, and the implications for future ambitions of national data curation in medical imaging to advance the safe adoption of artificial intelligence in healthcare.